How to choose between measures of tinnitus loudness for clinical research?: a report on the reliability and validity of an investigator-administered test and a patient-reported measure using baseline data collected in a phase IIa drug trial - Hall, Deborah A.; Mehta, Rajnikant; Fackrell, Kathryn L. (ASHA, 2017)
Purpose: Loudness is a major auditory dimension of tinnitus, and is used to diagnose severity, counsel patients or as a measure of clinical efficacy in audiological research. There is no standard test for tinnitus loudness, but matching and rating methods are popular. This article provides important new knowledge about the reliability and validity of an audiologist-administered tinnitus loudness matching test and a patient-reported tinnitus loudness rating. Method: Retrospective analysis of loudness data for 91 participants with stable subjective tinnitus enrolled in a randomised controlled trial of a novel drug for tinnitus. There were two baseline assessments (Screening, Day1) and a post-treatment assessment (Day28). Results: About 66-70% of the variability from Screening to Day1 was attributable to the true score. But measurement error, indicated by the Smallest Detectable Change, was high for both tinnitus loudness matching (20 dB) and tinnitus loudness rating (3.5 units). Only loudness rating captured a sensation that was meaningful to people with the lived experience of tinnitus. Conclusions: The tinnitus loudness rating performed better against acceptability criteria for reliability and validity than did the tinnitus loudness matching test administered by an audiologist. But the rating question is still limited because it is a single-item instrument and is probably able to detect only large changes (at least 3.5 points).